Successful Application of Extracorporeal Membrane Oxygenation in an Acute Tonsillitis Patient Complicated with Acute Respiratory Distress Syndrome: A Case Report - Zhang Z (Dove Medical Press, 2021)
Zhufeng Zhang,1 Dongmei Guo,2 Qi Ren3 1Emergency Department of Sandun District of Zhejiang Hospital, Hangzhou, Zhejiang, People’s Republic of China; 2Radiology Department of Sandun District of Zhejiang Hospital, Hangzhou, Zhejiang, People’s Republic of China; 3Qi Ren Intensive Care Unit of Sandun District of Zhejiang Hospital, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Qi RenIntensive Care Unit of Sandun District of Zhejiang Hospital, 1229th Gudun Road, Xihu District, Hangzhou, Zhejiang, 310030, People’s Republic of ChinaTel +86-18600754832Email xiewenzhangrenqi@163.comAbstract: Cases of acute tonsillitis, a common disease in the emergency department, are mostly mild and those complicated by severe pneumonia and acute respiratory distress syndrome are rarely reported.Keywords: acute tonsillitis, severe pneumonia, acute respiratory distress syndrome, extracorporeal membrane oxygenation, case report